PENGARUH PENGUNGKAPAN ENVIRONMENTAL, SOCIAL AND GOVERNANCE (ESG), GREEN ACCOUNTING, UKURAN PERUSAHAAN DAN KEPEMILIKAN INSTITUSIONAL TERHADAP NILAI PERUSAHAAN - Jinan, Sayyidah Shofiyatul; Atiqah (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
Firm value is an important indicator for investors in assessing a company's performance. This study analyzes the influence of ESG disclosure, green accounting, firm size, and institutional ownership on firm value in companies listed on the Indonesia Stock Exchange in the Consumer Non-Cyclicals, Basic Materials, Industrials, and Consumer Cyclicals sectors during the 2020–2024 period. The research employs a quantitative method using panel data regression and is processed using EViews 12. The results show that ESG disclosure, green accounting, and institutional ownership have a negative effect on firm value, while firm size has a positive effect. These findings highlight the importance of corporate strategies that balance financial performance and sustainability to attract market attention.